Identifying Research Trends and Gaps in the Context of Linux and Unix Security - Adriano, Raquel C.; Calayag, Jahleine Marielle M.; Cruz, Marian Minelli S.; Concepcion, Anthony U. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
Linux and Unix operating systems are fundamental to modern computing infrastructures, including cloud platforms, mobile devices, and supercomputers. With their increasing adoption, security has remained a persistent and evolving concern over the past two decades. This study conducts a systematic bibliometric analysis of 50 peer-reviewed journal articles and conference papers published between 2001 and 2020, segmented into four time periods: 2001–2005, 2006–2010, 2011–2015, and 2016–2020. Using citation analysis and co-word mapping via Mendeley and VOSviewer, the study identifies four main thematic clusters: (1) access control and authentication, (2) kernel-level vulnerabilities, (3) cloud and container security, and (4) mobile and Android-related threats. Early research focused on foundational topics such as system architecture and access control mechanisms, while more recent studies emphasized cloud-native security, virtualization, and mobile platform vulnerabilities. The analysis also reveals a significant disparity in research volume, with Linux-related studies dominating the field and Unix security receiving less than 20% of the total focus. This underrepresentation of Unix indicates a critical gap in the literature. These findings highlight not only the shifting priorities in open-source operating system security but also the need for renewed attention to Unix-specific threats and cross-platform security strategies in future research.